Analysis of water balance and moisture regions: A study of Jaunpur district, Uttar Pradesh - Anamika Singh (National Geographical Journal of India, 2024)
Climate plays a crucial role in shaping our physical environment, influenced significantly by geographical location and topographical factors. Key elements such as temperature, rainfall, humidity, atmospheric pressure, and winds define a region's climate. Human activities, such as agriculture, urbanization, deforestation, and industrialization, actively modify local climates. In geographical studies, the climatic water balance, including parameters like Potential Evapotranspiration (PET), Actual Evapotranspiration (AET), Water Surplus, and deficits, holds particular importance. These metrics help assess moisture availability, essential for determining irrigation schedules and understanding soil moisture levels critical for plant growth. Jaunpur, situated in a subtropical interior with a monsoon climate, experiences distinct seasonal weather variations. Analyzing these climatic factors and moisture adequacy aids in identifying suitable crops and optimal irrigation practices, crucial for agricultural planning and maintaining plant health.